PENGARUH PEMBERIAN KOMBINASI SARI KACANG DAN JAHE MERAH TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Dewi Andariya Ningsih; Hayatul Rahimah; Amelia Putri (LPPM Universitas Abdurrab, 2026)
Inadequate breast milk production is one of the barriers to successful exclusive breastfeeding among postpartum mothers. Factors such as improper breastfeeding techniques, stress, and a lack of knowledge and social support can exacerbate this condition. Several natural interventions, such as consuming red beans and red ginger, are believed to increase breast milk production. Red beans contain protein and phytoestrogens, while red ginger contains gingerol, which acts as a natural galactagogue. This study is a quantitative study with a quasi-experimental design using a two-group post-test approach. The intervention group was given a combination of red bean and red ginger extracts for 40 days, while the control group received a placebo. Data were collected through questionnaires and observations and analyzed using the Wilcoxon and Mann-Whitney tests. The objective was to determine the effect of administering a combination of red bean and red ginger extracts on increasing breast milk production in postpartum mothers in the service area of the Jambesari Bondowoso Community Health Center. The study was conducted from April to June 2025. Results: There was an increase in average breast milk production in the intervention group from 1.60 to 2.60. The Wilcoxon test showed a significant difference (p < 0.001) within the intervention group. The Mann-Whitney test showed a significant difference between the intervention and control groups. The combination of red bean and red ginger extracts is effective in increasing breast milk production in postpartum mothers. This intervention is recommended as a nonpharmacological alternative to increase breast milk production.